Sex differences in the strategies of spatial learning in prenatally-exposed rats treated with various drugs in adulthood - Macúchová, Eva; Nohejlová, Kateryna; Ševčíková, Mária; Hrebíčková, Ivana; Šlamberová, Romana (Behavioural brain research, 2017)
In the present study we investigated the sex differences in the effect of adult long-term drug treatment on cognitive functions of Wistar rats, which were prenatally exposed to MA (5mg/kg) or saline. Cognitive functions were tested as an ability of spatial learning in the Morris Water Maze (MWM), which consisted of three types of tests: "Place Navigation Test"; "Probe Test", and "Memory Recall Test". Adult animals were injected daily, after completion of the last trial, either with saline or cocaine (COC; 5mg/kg), MDMA (3,4-methylenedioxy-methamphetamine; 5mg/kg), morphine (MOR; 5mg/kg), or delta-9-tetrahydrocannabinol (THC; 2mg/kg). Results revealed worsened MWM performance in female rats after drug treatment in adulthood. Not only were traditionally investigated parameters affected by drug treatment (latency of platform acquisition, search strategy, distance traveled), but also strategies used by animals (thigmotaxis, scanning). Analyses of search strategies observed in the Place Navigation Test, as well as in the Memory Recall Test, demonstrated variations in the percentage of time spent in thigmotaxis and scanning in females after treatment with COC, MDMA, MOR, and THC. Although we did not see a sensitizing effect of prenatal MA, in some cases the effect of drug treatment in adulthood differed depending on the prenatal drug exposure. The data presented in this study demonstrates that exposure to drugs with various mechanisms of action alters spatial abilities of female rats in the MWM. Alterations in the effect of adult drug treatment with reference to prenatal drug exposure were also found in the present study.
Keywords: Prenatal Exposure Delayed Effects; Dronabinol; Pregnancy; Male; N-Methyl-3,4-methylenedioxyamphetamine; pohlavní dimorfismus; Sex differences; Psychotropic Drugs; psychotropní léky; potkani Wistar; Morphine; psychologické testy; Animals; kokain; náhodné rozdělení; Spatial Learning; N-methyl-3,4-methylendioxyamfetamin; morfin; Morris Water Maze; Spatial Navigation; Sex Characteristics; Spatial learning; zvířata; Random Allocation; prostorová navigace; prostorové učení; kognice; mužské pohlaví; Cocaine; Long-term drug treatment; tetrahydrokanabinol; Cognition; Psychological Tests; Rats, Wistar; ženské pohlaví; methamfetamin; těhotenství; Female; Methamphetamine; zpožděný efekt prenatální expozice